Saturn run - Sandford, John, 1944 February 23-; Ctein (New York : G. P. Putnam's Sons, an imprint of Penguin Random House LLC, 2015)
In 2066, a Caltech intern notices an anomaly approaching Saturn, and decelerating think it is a spaceship. Government officials concur and want to get it first. So the race is on with the Chinese to find whether the anomaly is a spaceship and be the first to capture it.
Keywords: Space ships -- Fiction; Quests (Expeditions) -- Fiction; Science fiction; Adventure fiction